IMPLEMENTASI METODE ACTIVITY BASED COSTING TERHADAP PERHITUNGAN BIAYA PRODUKSI TEMPE PADA USAHA MIKRO “DUA PUTRI“ KELURAHAN BAKUNASE KOTA KUPANG - Ana Yunita. K Muda; Sondang S. P. Pudjiastuti; Yacobus C. W. Siubelan; Tomycho Olviana (Buletin Ilmiah Impas, 2023)
This study aims to implement the Activity Based Costing (ABC) method in calculating production costs because it can provide more accurate cost-related information and become a reference for determining selling prices using the Cost Plus Pricing method and calculating profits in the "Dua Putri" Micro Business, Bakunase Village, Kupang City. The results of this study indicate that the calculation of production costs using the Activity Based Costing method includes the first stage of tracing costs to activities consisting of identifying activities, allocating costs to activities, determining homogeneous cost groups and determining group rates and the second stage tracing costs to products where factory overhead costs are assigned. using the cost driver of each product and producing production costs for January Rp.45.260.256, February Rp.40.997.256 and March Rp.35.153.256 then for determining the selling price of products using the Cost Plus Pricing method is greater than the determination of product selling prices by micro and small businesses The net profit earned by micro enterprises after deducting the cost of raw materials, labor costs, overhead costs and income tax for three months for January is Rp.9.643.844, February is Rp.8.593.544 and March is Rp.7.353.144.